Pengaruh Kualitas Pelayanan dan Promosi terhadap Keputusan Pembelian : (Studi Kasus Konsumen Kita Bersama Swalayan Bulakamba) - Ela Febriani; Hendri Sucipto; Roby Setiadi (JURNAL RISET MANAJEMEN (JURMA), 2023)
This research aims to analyze the influence of service quality and promotion on purchasing decisions in the consumer case study of Kita Bersama Swalayan Bulakamba. The type of this research is quantitative descriptive. In this study, researchers obtained 100 samples calculated from a population of 2,451 using the slovin formula at an error rate of 10%. The method used in this study uses Multiple Linear Regression Analysis. The data collection technique is by distributing questionnaires to respondents using Google from. The results of this study indicate from the t test which states that the service quality variable influences purchasing decisions with a calculated t value of service quality of 6.344 > t table 0.1660 with a significant value of 0.000 <0.05 and promotion has a positive and significant effect on purchasing decisions with promotion t-count 14.655 > t-table 0.1660 with a significant value of 0.000 <0.05.